The imaginary of personalization in relation to platforms and teacher agency in Denmark - Rasmus Leth Jørnø; Bjarke Lindsø Andersen; Peter Gundersen (Taylor & Francis Group, 2022)
In this theoretical paper, we argue that Tech enthusiasts and skeptics are animated by the same sociotechnical personalization imaginary to improve education and teaching through personalization, but see very different paths to this goal. Tech boosters point to well-known problems of the existing education system - and rhetorically ask: 'why shouldn't we solve these problems with technology?' Doomsters claim that only humans can do this and ask 'why should we relinquish power to machines?' We believe that the full implications of incorporating adaptive technologies in schools have neither been considered, fully revealed, or adequately prepared for by either side. But we are not interested in evaluating either the claims of techboosters or doomsters. Through an analysis through the lens of imaginaries, we reveal the false dichotomy of for or against technology, which obfuscates the fundamental question of whether the social technology we have put in place to educate ourselves solves the right problem and solves the problem well? We conclude with a brief discussion on the value of the personalization imaginary. We argue that the question is not whether platforms enable or disable teacher agency per se, but rather why should we hold up personalization as an ideal for education?